2010
DOI: 10.3113/fai.2010.0153
|View full text |Cite
|
Sign up to set email alerts
|

Plantar Pressure and Foot Pain in the Last Trimester of Pregnancy

Abstract: We believe that based on the observed pressure changes, foot pain in pregnancy due to changes in body mass and distribution may be relieved by exercise and shoewear modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 19 publications
3
48
2
1
Order By: Relevance
“…UnluOzkan e Basgul [17] encontraram aumento da pressão plantar no antepé no último trimestre gestacional, durante tarefas estáticas e dinâmicas. Por outro lado, durante o mesmo período, Gaymer et al [18] observaram aumento da pressão no mediopé, a qual retornou aos valores normais após a gestação.…”
Section: Discussionunclassified
“…UnluOzkan e Basgul [17] encontraram aumento da pressão plantar no antepé no último trimestre gestacional, durante tarefas estáticas e dinâmicas. Por outro lado, durante o mesmo período, Gaymer et al [18] observaram aumento da pressão no mediopé, a qual retornou aos valores normais após a gestação.…”
Section: Discussionunclassified
“…In contrast to the study by Gaymer et al (26), we found that increased midfoot plantar pressure was related to pain. Various researchers reported that foot alterations due to the increase in body weight as well as hormonal changes during pregnancy played roles in foot pain (3,27).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy‐related changes in trunk motion during a walking task may indicate altered musculoskeletal loads with potential for injury or pain, and pregnancy was shown to induce significant changes in postural control when women stood with a reduced support base (12). Progression of symptoms is seen especially in the third trimester as the center of gravity changes due to weight gain (20). Pregnancy may result in strain symptoms in the lumbosacral region and pelvis, with variable pain intensifying in various static positions (21).…”
Section: Discussionmentioning
confidence: 99%